Tracing changes in the diet and habitat use of black-tailed godwits in Western France, using a stable isotope approach. Issue 3 (4th May 2018) - Robin, Frédéric; Delaporte, Philippe; Rousseau, Pierre; Meunier, Francis; Bocher, Pierrick
ABSTRACT: Western France is at the crossroads of the migratory routes of two subspecies of black-tailed godwit, Limosa limosa . After leaving Iceland, the godwit L.l. islandica Icelandic black-tailed godwit (IBTG) winters on the coast of western Europe, while the continental black-tailed godwit (CBTG) L.l. limosa can stop in France when migrating between Iberia or Africa and their main breeding grounds in the Netherlands. In this study, we analysed δ 15 N and δ 13 C from flight feathers and whole blood throughout the non-breeding period to trace variations in habitat use for both subspecies on the western French coast. Adults and juveniles of IBTG adopt the same feeding habitats as soon as they arrive in the study area, progressively losing the Icelandic freshwater habitat signal, and becoming clearly restricted to marine habitats in winter. Some individuals begin to move locally to freshwater habitats, joining CBTG in a stopover at the end of the wintering period in preparation for northward migration.